The Influence of Communication and Work Environment on Employee Discipline at the Islamic Hospital Bontang - Agusyani, Agusyani; Nurfauziah, Adinda Alya; Larashati, Yunita Bunga Dina (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This research was conducted to determine The Influence Of Communication And Work Environment On Employee Work Discipline Of Bontang Islamic Hospital Employess. The respondents of this research were 72 respondents who were employees at the Bontang Islamic Hospital who could be used in data management. The data was processed using correlation analysis with the help of an analysis tool, namely SPSS version 25.0. This type of research uses quantitative research. The data collection techniques used in this research were questionnaire methods, documentation, interviews, observation and literature study. The analytical method used in this research is a quantitative descriptive method. The data analysis techniques used in this research are data quality testing, classical assumption testing, multiple linear regression testing and hypothesis testing. Based on the research results, it can be seen from the partial results that Communication (X1) has a significant effect on Work Discipline (Y), partially the Work Environment (X2) has a significant effect on Work Discipline (Y). Based on the simultaneous results, the variables Communication (X1) and Work Environment (X2) have a significant effect on Work Discipline (Y). So the results of this research indicate that Communication and Work Environment of Bontang Islamic Hospital have an influence in improving employee work discipline.